Psychoeducation on Bullying Behaviour in Grade 6 Students of Public Primary School 06 Tanjung Batu - Arisandy, Desy; Amaniah, Shella Zahara (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: Awareness of bullying’s negative impacts has grown significantly. Many studies highlight its physical, emotional, and psychological effects on both victims and perpetrators. Method: The methods used in this community service are observation, interview, and socialization in Public Primary School 06 Tanjung Batu. Practical Application: The psychoeducation program effectively helped students understand the importance of respecting differences, showing empathy, and maintaining positive social relationships. Conclusion: Psychoeducation for grade 6 students at SDN 06 Tanjung Batu improved understanding of bullying from both the victim’s and perpetrator’s perspectives. Using materials, animated videos, ice breaking, discussions, and quizzes, students recognized types of bullying, its impacts, and ways to respond positively. The program promoted empathy, respect, and social harmony, contributing to a safer school environment.